Polyamide nanofilm composite membranes (NCMs) supported by chitosan-coated polyvinyldenefluoride (PVDF) nanofibrous mats and their separation properties. Issue 50 (26th October 2016) - Xu, Guo-Rong; Zhao, He-Li; Wu, Shui-Bo
Abstract: Desalination provides an effective method to solve the problem of freshwater shortage, which is currently the most urgent issue around the world. Among all the desalination methods, membrane desalination is superior to others due to its unique advantages, such as easy operations and high separation performance. Specially, polyamide thin-film composite (PA-TFC) reverse osmosis membranes are the dominant desalination membranes in recent decades and have been widely used all around the world. However, the comparatively high operating pressures and low water permeations make them non cost-effective and have seriously restricted their wider applications. Electrospun nanofibrous membranes (ENMs) have shown great promising applications in the filtration areas. ENMs-based filtration membranes can provide higher permeations under the same operating conditions. Therefore, in the current work, a novel PA-TFC membrane supported by ENMs is designed. The ENMs-supported PA-TFC membranes show apparently high water flux (2.06 L m −2  h −1  bar −1 ) with a salt rejection of 94.4%. More importantly, the operating pressure is only 8 bar, which is lower than most of the currently used and researched PA-TFC membranes. The fabricated membranes are more cost-effective and can be used in some unique desalination areas which need as high as permeations and moderate salt rejections.